Diseño y construcción de una incubadora automática para canes con sistema de monitoreo y control de temperatura, humedad y oxigenación del aire con visualización a través de una app y cámara web - Moposita Muzo, Mauricio Alexander (2023)
This project describes the design and construction of an incubator for raising puppies that allows care during the neonatal period or recovery period from their illness, for which temperature, humidity and air oxygenation variables are controlled inside. of the passenger compartment; A type of PID control has been developed for the temperature variable, air oxygenation and an on-off control for the humidity variable.